Handbook of Florida Agricultural Laws: Related Non-Crop or Product Agricultural Topics - Michael T. Olexa; Connor Brock (EDIS, 2022)
This revised document is part of the Handbook of Florida Agricultural Laws, which was designed to provide an accurate, current, and authoritative summary of the principal Florida laws that directly or indirectly relate to agriculture. It provides a basic overview of the many rights and responsibilities that farmers and farm land owners have under Florida laws. Many readers may value this handbook because it informs them about these rights and responsibilities, and it provides them with good contacts for more detailed information. However, the reader should be aware that because the laws, administrative rulings, and court decisions on which this handbook is based are subject to constant revision, portions of this handbook could become outdated at any time. Many details of cited laws are also left out due to space limitations.